2022
DOI: 10.1111/maps.13905
|View full text |Cite
|
Sign up to set email alerts
|

The chondrite breccia of Antonin (L4‐5)—A new meteorite fall from Poland with a heterogeneous distribution of metal

Abstract: On July 15, 2021, a huge fireball was visible over Poland. After the possible strewn field was calculated, the first and so far only sample, with a mass of 350 g, was discovered 18 days after the fireball event. The Antonin meteorite was found August 3, 2021, on the edge of a forest close to a dirt road near Helenow, a small suburb of the city of Mikstat. The rock is an ordinary chondrite breccia and consists of equilibrated and recrystallized lithologies. The boundaries between different fragments are difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 79 publications
4
7
0
Order By: Relevance
“…This alternative would be in agreement with observations of Bischoff et al. (2022), who studied another part of Antonin sample and concluded it is an S4 chondrite. Whether Antonin records post‐shock annealing and “secondary” shock or is highly heterogeneously deformed cannot be concluded with our data and needs further study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This alternative would be in agreement with observations of Bischoff et al. (2022), who studied another part of Antonin sample and concluded it is an S4 chondrite. Whether Antonin records post‐shock annealing and “secondary” shock or is highly heterogeneously deformed cannot be concluded with our data and needs further study.…”
Section: Discussionsupporting
confidence: 92%
“…It is, however, also likely that the Antonin responded very heterogeneously to shock wave, resulting in uneven record of peak shock pressures experienced. This alternative would be in agreement with observations of Bischoff et al (2022), who studied another part of Antonin sample and concluded it is an S4 chondrite. Whether Antonin records post-shock annealing and "secondary" shock or is highly heterogeneously deformed cannot be concluded with our data and needs further study.…”
Section: Reconstruction Of Shock Processes and Parent Body Evolutionsupporting
confidence: 92%
See 2 more Smart Citations
“…Details about the analytical techniques are given elsewhere in Pack et al (2016) and Peters et al (2020;also, compare Herwartz et al, 2014;Pack et al, 2017). As was done earlier for the Antonin chondrite, another recent fall of an L chondrite breccia (Bischoff, Patzek, et al, 2022), the δ 17 O and δ 18 O values are reported on the VSMOW (Vienna Standard Mean Ocean Water) scale, and the Δ 017 O is defined here as:…”
Section: Oxygen Isotope and Bulk Chemical Analysesmentioning
confidence: 99%